The movement into cinema as a stage in the cinema development - Toporivska, Yaroslava; Dyadyukh-Bogatko, Nataliya; Belinska, Lyudmila; Balan, Nataliia; Patsaliuk, Liliia (Ìstorìâ nauki ì tehnìki (Kiïv. Online), 2025)
The development of moving images is a multi-layered abstraction of movement in visual space, based on optical, mechanical, photographic and theoretical innovations. Each stage contributed to the creation of modern cinema in its technical and conceptual forms. The main aim of this study is to identify and analyze how scientific and technical discoveries in the fields of optics, physiology of vision, mechanics and chemistry became the basis for the emergence of a new art form – cinema, and also to show how the interaction of science, technology, culture and society contributed to the formation of a completely new system of visual thinking and mass communication. The article analyzes the history of the emergence of moving images – from optical toys of the 19th century to modern digital cinema. The emphasis is on technical, psychophysiological and technological development, as well as on modern directions that continue the evolution. The ideal “frame–interval–frame” (blackout, break) was a breakthrough in the 19th century, but it was digital technologies that gave freedom to the narrative, mixing frames in real time, adding intellectual processing and visual effects. The subject of the study was the study of the formation of scientific, technical and cultural prerequisites that led to the emergence of cinematography as a result of the evolution of knowledge about visual perception and technologies for fixing and reproducing dynamic images. Particular attention was focused on research in the field of physiology of vision, in particular on the phenomenon of persistence of visual image, which explained the illusion of movement between individual frames. The influence of technical achievements on the development of optical devices that simulated image movement, as well as the analysis of experiments with chronography, was considered. The study paid special attention to the invention of recording and projection devices. All this was considered in the context of socio-cultural and commercial processes, such as the emergence of cinemas, fair screenings, and the formation of cinema as a public spectacle. Thus, the subject of the study is not only the technical inventions themselves, but also the deeper processes of interaction of science, technology and culture, which together led to the emergence of a new means of mass communication – cinema.